Enhanced field-of-view structured illumination projector using stacked microlens arrays - Kundu, Rohan; Schreiber, Peter; Dannberg, Peter; Fischer, Stephanie; Li, Chen; Zeitner, Uwe; Tuennermann, Andreas (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
Current LED based structured illumination projectors use commercial objective lenses to project the pattern, leading to an increased size of the projector. We present a compact, pseudo-random pattern generator with an enhanced field of view (FOV) of 60° × 60° to project structured light for machine vision applications. The miniaturization of optics is achieved by utilizing the multi-aperture approach. Currently such multi-aperture projection optics have an FOV of about 20°. Enlarging the FOV of microlenses results in higher geometric aberrations. Aberration correction for wide FOV is done by distributing the optical power over several microoptical surfaces, as in traditional optical systems, leading to a design of stacked microoptics. The correction of dominant aberrations like astigmatism is done by employing anamorphic microlenses. Further enhancement of the FOV is achieved by continuously varying the FOV of the individual lenslets over the microlens array (MLA). Thus, every channel of the array projects light to a different region of the image plane, resulting in a symmetric and continuous filling of the FOV across the image field. Consequently, anamorphic irregular or 'chirped' MLAs with lenslets of varying focal length and orientation depending upon its location in the MLA are designed. This also requires the projection optics to be illuminated with a field dependent incidence for which a two lens condenser optic is designed. A regular condenser lens array couples the light into the channels similar to the scheme for Köhler illumination, while the stacked microoptics along with a bulk field lens image the slide object on to the projection plane. A corresponding prototype with stacked and chirped microoptics with buried apertures and slide structures is realized using advanced reflow technology and characterization of such an arrayed pattern projector is presented.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Array projection; Gesture recognition; Microlens arrays; Microoptics; Ray fan generator; Reflow technology; Structured illumination